(untitled) (Nigerian Journal of Technology, 2022)
Humans and the environment are both concerned about contaminated drinking water. One of the most dangerous constituents in wastewater is heavy metals. The removal of these contaminants from the ecosystem is still a challenge. Some of these heavy metals have been toxic concentrations in human and livestock drinking water. As a result, the goal of this study was to compare the adsorption potential of non-treated and acid-treated activated carbon generated from maize cob in the treatment of wastewater. Fresh maize cobs were air-dried and oven-dried at 255 °C for 9 hours after being cleaned in distilled water. These were crushed, sieved through a 300 µm mesh and carbonized in a muffle furnace to produce powdered activated carbon (PAC). One half of PAC was treated with 780 mL of hydrochloric acid (acid-treated activated carbon - AAC), while the other received no further treatment (non-treated activated carbon - NAC). For surface characteristics and functional groups, the conventional approach was applied to characterize AAC and NAC. Thirty grams of each sample were used in the treatment of metal recycling effluent. Untreated (T1), filtered (T2), NAC treated (T3), and AAC treated (T4) wastewater samples were analysed in three replicates using World Health Organization (WHO) and Lagos State Environmental Protection Agency (LASEPA) standard methods for Physico-chemical parameters. Analysis of data was by ANOVA, while mean separation was by Duncan’s Multiple Range Test (DMRT) at (P ≤ .05). Results showed that T2 had no significant improvement (P ≤ .05) in all parameters tested. T3 significantly increased pH, conductivity, TS and TSS, gave the highest mean alkalinity, but showed no significant changes in heavy metal contents. T4 significantly improved mean colour, conductivity, nitrate content and DO, reduced mean pH (from 7.4±0 to 2.1±0.1), increased heavy metal concentrations (P ≤ .05) and increased mean total acidity, but not significantly (P ≥ .05). Treatments improved parameters in the following order: filtration < NAC < AAC. Thus, acid-activated carbon had a higher adsorbent capability than non-activated carbon due to its wide surface area and low moisture and ash contents.